Calpain-mediated proteolysis as driver and modulator of polyglutamine toxicity - Incebacak Eltemur, Rana Dilara; Nguyen, Huu Phuc; Weber, Jonasz Jeremiasz (Frontiers in Molecular Neuroscience, 2022)
Among posttranslational modifications, directed proteolytic processes have the strongest impact on protein integrity. They are executed by a variety of cellular machineries and lead to a wide range of molecular consequences. Compared to other forms of proteolytic enzymes, the class of calcium-activated calpains is considered as modulator proteases due to their limited proteolytic activity, which changes the structure and function of their target substrates. In the context of neurodegeneration and - in particular - polyglutamine disorders, proteolytic events have been linked to modulatory effects on the molecular pathogenesis by generating harmful breakdown products of disease proteins. These findings led to the formulation of the toxic fragment hypothesis, and calpains appeared to be one of the key players and auspicious therapeutic targets in Huntington disease and Machado Joseph disease. This review provides a current survey of the role of calpains in proteolytic processes found in polyglutamine disorders. Together with insights into general concepts behind toxic fragments and findings in polyglutamine disorders, this work aims to inspire researchers to broaden and deepen the knowledge in this field, which will help to evaluate calpain-mediated proteolysis as a unifying and therapeutically targetable posttranslational mechanism in neurodegeneration.